Predisposing Factors Associated with Longer Hospital Stay in Children Less Than 5 Years of Age with Severe Lower Respiratory Tract Infection (Medical Forum Monthly, 2023)
Objective: To determine the predisposing risk factors associated with longer duration of hospitalisation of children aged 2-59 months with severe Lower respiratory tract infection (LRTI).Study Design: Observational / descriptive / cross sectional studyPlace and Duration of Study: This study was carried out in the Children Hospital, Islamabad from October 2011 to March 2014.Materials and Methods: We enrolled 606 children aged 2-59 months with severe LRTI and at enrolment, complete history of present illness, physical examination, and necessary laboratory investigations were done. Enrolled children were managed according to the hospital’s standard protocols. Multivariate logistic regression analyses was conducted to determine the independent factors associated with longer duration of hospitalisation.Results: The mean (sd) age of children was 7.45 (8.41) months and 63% were male. Of 606 children, 241 (40%) had longer hospital stay (>3 days).Children whose mothers used biomass energy as fuel for cooking at home (AOR 3.63, p<0.0001), children who had history of vomiting (AOR 1.74, p=0.014), had duration of illness before presenting to hospital was >7 days (AOR 1.90, p=0.040), were unvaccinated (AOR 2.54, p=0.001), had lower mean serum calcium levels (AOR 0.08, p<0.0001), had positive CRP (AOR 4.67, p<0.0001), were severely anaemic (AOR 6.28, p=0.017) or were underweight (AOR 1.64, p=0.013) had significantly longer hospitalisation compared to their counterparts.Conclusion: The current study identified independent risk factors which lead to longer hospitalisation in children aged 2-59 months with severe LRTI. Findings of the current study would help paediatricians for better management of severe LRTI in under 5 children.